2012
DOI: 10.1002/mop.26863
|View full text |Cite
|
Sign up to set email alerts
|

A multiband hybrid antenna with double layer structures for mobile devices

Abstract: fiber end under test and the fiber for detection were measured at 1.31-and 1.55-lm wavelengths using laser diodes (LDs), an optical power meter (OPM), and 3-dB coupler. When both the measured return losses at those two wavelengths were equal to $14.7 dB (from 14.7 to 15.7 dB in our experiments), the part of the fiber end under test could be identified as uneven [shown in Fig. 1 (a)]. If one of the two losses is not equal to $14.7 dB, the part can be identified as flat [shown in Fig. 1(b)]. Every part of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…As an example mobile phone antennas use multiband filters to split the different frequency bands (Anguera, Andújar, Huynh Orlenius, & Picher Puente, 2013;Anguera, Andujar, & Garcia 2013;Sim, Chao, & He, 2012;Wong, 2003). This has led to extensive research in multiband BPF design with some dual-band BPF being reported in Feng and Shao (2006), Chang and Sun (2006), Chin and Yeh (2009), Zhang, Jiao, Wang, and Cao (2011), Zhang, Chen, Xue, and Li (2007), Luo, Qian, Ma, and Yeo (2010), Wu, Liang, Qin, and Li (2008) and Ghatak, Pal, Sarkar, and Poddar (2012).…”
Section: Introductionmentioning
confidence: 99%
“…As an example mobile phone antennas use multiband filters to split the different frequency bands (Anguera, Andújar, Huynh Orlenius, & Picher Puente, 2013;Anguera, Andujar, & Garcia 2013;Sim, Chao, & He, 2012;Wong, 2003). This has led to extensive research in multiband BPF design with some dual-band BPF being reported in Feng and Shao (2006), Chang and Sun (2006), Chin and Yeh (2009), Zhang, Jiao, Wang, and Cao (2011), Zhang, Chen, Xue, and Li (2007), Luo, Qian, Ma, and Yeo (2010), Wu, Liang, Qin, and Li (2008) and Ghatak, Pal, Sarkar, and Poddar (2012).…”
Section: Introductionmentioning
confidence: 99%